Are soybean yields getting a free ride from climate change? Evidence from Argentine time series data - Hildegart A. Ahumada; Magdalena Cornejo (Econometrics, 2021)
We analyze the influence of climate change on soybean yields in a multivariate time-series framework for a major soybean producer and exporter-Argentina. Long-run relationships are found in partial systems involving climatic, technological, and economic factors. Automatic model selection simplifies dynamic specification for a model of soybean yields and permits encompassing tests of different economic hypotheses. Soybean yields adjust to disequilibria that reflect technological improvements to seed and crops practices. Climatic effects include (a) a positive effect from increased CO2 concentrations, which may capture accelerated photosynthesis, and (b) a negative effect from high local temperatures, which could increase with continued global warming.
Keywords: 330; climate change; CO2; soybean yields; technology; temperature